2017
DOI: 10.1089/acu.2017.1225
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation and Treatment of Human Papilloma Virus-Related Warts with Energetics of Living Systems Acupuncture

Abstract: Background: Cutaneous warts are small skin lesions formed as a result of infection by the human papilloma virus (HPV). In the lesion, viral manipulation creates a microenvironment that favors virus survival and reproduction. Most lesions eventually regress, probably as a result of a Th1-mediated immune response. However, some warts fail to regress and become persistent. Objective: The efficacy of treatment of persistent HPV-caused warts with Energetics of Living Systems acupuncture and monitored immune system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… 36 A significant proportion of TCM research focuses on botanical preparations; however, TCM is often a combination of techniques that have been shown to alter immune response and anti-inflammatory effect. 37 - 40 Due to the multiplicity of interventions available within TCM, this study focused on botanical/herbal medication and acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“… 36 A significant proportion of TCM research focuses on botanical preparations; however, TCM is often a combination of techniques that have been shown to alter immune response and anti-inflammatory effect. 37 - 40 Due to the multiplicity of interventions available within TCM, this study focused on botanical/herbal medication and acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of the condition cannot be predicted (Lynch, Cliffe, & Morris-Jones, 2014). The spontaneous resolution of warts is Th1-cell mediated and it is usually followed by immune memory that protects the host from future infection (Brustin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Yun et al reported that 19-22 weeks of moxibustion treatment can effectively eliminate warts 11 . According to Brustin et al, the therapeutic effect of acupuncture on persistent warts is related to the immune response and anti-inflammatory effects 15 . Performing acupuncture and moxibustion therapy for children is difficult because they are afraid of the treatment, and there is a risk of burns.…”
Section: Discussionmentioning
confidence: 99%